Hepatitis B virus PreS1 facilitates hepatocellular carcinoma development by promoting appearance and self-renewal of liver cancer stem cells. (1st August 2017) - Liu, Zhixin; Dai, Xuechen; Wang, Tianci; Zhang, Chengcheng; Zhang, Wenjun; Zhang, Wei; Zhang, Qi; Wu, Kailang; Liu, Fang; Liu, Yingle; Wu, Jianguo
Abstract: Hepatitis B virus (HBV) is a major etiologic agent of hepatocellular carcinoma (HCC). However, the molecular mechanism by which HBV infection contributes to HCC development is not fully understood. Here, we initially showed that HBV stimulates the production of cancer stem cells (CSCs)-related markers (CD133, CD117 and CD90) and CSCs-related genes (Klf4, Sox2, Nanog, c-Myc and Oct4) and facilitates the self-renewal of CSCs in human hepatoma cells. Cellular and clinical studies revealed that HBV facilitates hepatoma cell growth and migration, enhances white blood cell (WBC) production in the sera of patients, stimulates CD133 and CD117 expression in HCC tissues, and promotes the CSCs generation of human hepatoma cells and clinical cancer tissues. Detailed studies revealed that PreS1 protein of HBV is required for HBV-mediated CSCs generation. PreS1 activates CD133, CD117 and CD90 expression in normal hepatocyte derived cell line (L02) and human hepatoma cell line (HepG2 and Huh-7); facilitates L02 cells migration, growth and sphere formation; and finally enhances the abilities of L02 cells and HepG2 cells to induce tumorigeneses in nude mice. Thus, PreS1 acts as a new oncoprotein to play a key role in the appearance and self-renewal of CSCs during HCC development. Highlights: HBV stimulates the appearance and production of liver cancer stem cells (CSCs). PreS1 gene of HBV acts as a new oncoprotein in human liver cells. PreS1 gene play a key role in the appearance of CSCs during HCC development.